Analysis of fatal intracranial hemorrhage in 792 acute leukemia patients - H Kim; JH Lee; SJ Choi; WK Kim; JS Lee; KH Lee (Haematologica, 2004)
Forty-one of 792 acute leukemia patients suffered fatal intracranial hemorrhage (FICH). Acute promyelocytic leukemia was the most common subtype. Achievement of complete remission in AML was significantly influenced by FICH. FICH accounts for about half of deaths from hemorrhage and this proportion has not changed despite improvements in leukemia management.